A dosimetric comparison of 3D conformal vs intensity modulated vs volumetric arc radiation therapy for muscle invasive bladder cancer - Foroudi Farshad; Wilson Lesley; Bressel Mathias; Haworth Annette; Hornby Colin; Pham Daniel; Cramb Jim; Gill Suki; Tai Keen; Kron Tomas (Radiation Oncology, 2012)
Abstract Background To compare 3 Dimensional Conformal radiotherapy (3D-CRT) with Intensity Modulated Radiotherapy (IMRT) with Volumetric-Modulated Arc Therapy (VMAT) for bladder cancer. Methods Radiotherapy plans for 15 patients with T2-T4N0M0 bladder cancer were prospectively developed for 3-DCRT, IMRT and VMAT using Varian Eclipse planning system. The same radiation therapist carried out all planning and the same clinical dosimetric constraints were used. 10 of the patients with well localised tumours had a simultaneous infield boost (SIB) of the primary tumour planned for both IMRT and VMAT. Tumour control probabilities and normal tissue complication probabilities were calculated. Results Mean planning time for 3D-CRT, IMRT and VMAT was 30.0, 49.3, and 141.0 minutes respectively. The mean PTV conformity (CI) index for 3D-CRT was 1.32, for IMRT 1.05, and for VMAT 1.05. The PTV Homogeneity (HI) index was 0.080 for 3D-CRT, 0.073 for IMRT and 0.086 for VMAT. Tumour control and normal tissue complication probabilities were similar for 3D-CRT, IMRT and VMAT. The mean monitor units were 267 (range 250–293) for 3D-CRT; 824 (range 641–1083) for IMRT; and 403 (range 333–489) for VMAT (P < 0.05). Average treatment delivery time were 2:25min (range 2:01–3:09) for 3D-CRT; 4:39 (range 3:41–6:40) for IMRT; and 1:14 (range 1:13–1:14) for VMAT. In selected patients, the SIB did not result in a higher dose to small bowel or rectum. Conclusions VMAT is associated with similar dosimetric advantages as IMRT over 3D-CRT for muscle invasive bladder cancer. VMAT is associated with faster delivery times and less number of mean monitor units than IMRT. SIB is feasible in selected patients with localized tumours.